Promoting Malaysia through “fertility tourism” / Siti Syairah Mohd Mutalip - Mohd Mutalip, Siti Syairah (UiTM Press, 2012)
The practice of ‘fertility tourism’ has been incredibly demanding and issues of couples border-crossing between nations has been extensively reported. Couples are known to have a wide variety of choices in their preferences in choosing countries for treatment. In search of the exact reason behind their willingness to go beyond borders to seek for best treatment, it is identified that there are two main reasons underlying ‘fertility tourism’ which is the legal and financial evasion. In comparison to Malaysian scenario, it is undeniable that Malaysia also is restricted to some of the fertility services due to Islamic law, but this should not be a barrier to promote the country to be one of the favorite choices for fertility tourists worldwide. For this to happen, it needs a great hand-to-hand teamwork and effort from all including from the service providers, tourism agents, public and others.